PEMBERDAYAAN UMKM MELALUI SERTIFIKASI HALAL GUNA MEMBANGUN EKONOMI BERBASIS SYARIAH DI DESA PLUMBON - Choirul Anwar; Sepia Hartiningsih; Muhammad Ichdal Umam; Hanun Tsabita Artana; Mujib Sahli (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2025)
The empowerment of MSMEs (Micro, Small, and Medium Enterprises) in Plumbon Village, Suruh Subdistrict, Semarang Regency through halal certification aims to enhance the sharia-based economy. This initiative involves socialization and mentoring for MSME actors to obtain halal certification, which is a crucial step in expanding market access and boosting consumer confidence. With active community participation and government support, this program successfully increased MSME actors' awareness of the importance of halal certification and motivated them to obtain it. As a result of this activity, several MSME actors in Plumbon Village successfully issued halal certificates, which is expected to strengthen the local economy, create new job opportunities, and build a sustainable sharia economic ecosystem in Plumbon Village.